G535(P) Do treatments for paediatric chronic fatigue syndrome improve pain? a systematic review. (25th October 2020) - Ascough, C; King, H; Serafimova, T; Jackson, S; Beasant, L; Brooks, JCW; Pickering, AE; Crawley, E
Abstract : Aims: Paediatric chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is common (prevalence 1–2%). Two thirds of children experience moderate or severe pain, and this is associated with increased fatigue and poorer physical function. However, current treatment approaches do not target pain. This systematic review aims to identify whether specialist treatment of paediatric CFS/ME improves pain. Methods: We conducted a detailed search in MEDLINE, EMBASE, PsycINFO, and the Cochrane Library. Two researchers independently screened texts published since 1994 with no language restrictions. We searched trial registration websites for unpublished trials and hand searched reference lists of all included studies. Inclusion criteria were (1) RCTs & observational studies; (2) Participants aged <19 years with CFS/ME; 3) Measure of pain (quantitative, qualitative, or mixed methods) before and after an intervention. Results: Of 1898 papers screened, 27 studies investigated treatments in paediatric CFS/ME, 20 of which did not measure pain. Only 5 treatment studies measured pain at baseline and follow-up and were included in this review. Four of the studies investigated behavioural interventions and one study investigated a pharmacological intervention (low dose clonidine). None of the interventions were specifically targeted at treating pain. Pain measures used were heterogenous and included a Visual Analogue Scale, CHQ-87 Bodily Pain Subscale, Brief Pain Inventory and a mean Daily Observed Pain score. Of the included studies 2 showed no improvement in pain scores with treatment, 1 small study described an improvement in pain in one subgroup, and 2 studies identified improvements in pain measures in 'recovered' patients compared to 'non-recovered patients'. Conclusion: Despite the prevalence and impact of pain in children with CFS/ME surprisingly few treatment studies measured pain. In those studies that did measure pain, there is limited evidence that treatment helps improve pain scores. However, patients who recover appear to have less pain than those who do not recover. More studies are needed to determine if pain in paediatric CFS/ME requires a specific treatment approach, with particular focus on patients who do not recover following initial treatment.